Pencitraan Desain Kemasan Oleh-Oleh Jepang - Meilani, Meilani (Bina Nusantara University, 2014)
Packaging has been done long ago with a simple function that is just as protective products. Packaging is made to facilitate transactions between merchants and buyers to consider the protective factors of products of long distance travel. However, over the times, packaging has undergone a shift in priorities. Packaging is no longer merely as a protector, especially with the amount of competition between product spread on the market. Packaging should be altered so that the product is easy to remember by the community and achieve the expected sales figures. That requires some graphic factors carefully planned and through in-depth research in order to produce an attractive packaging design, global and wanted by the community. In this paper, the research object is the packaging for souvenirs from Japan, which in recent years, become a topic of conversation in the community, not only in Japan even in the world. The writing is compiled using literature study approach and study data from an electronic network used as the primary source of information from this research. With good packaging design, imaging dignity of a product will go up and get the attention of potential buyers.